HERE AND OVERSEAS: LETTERS FROM RIO DE JANEIRO BY JAIME VITOR - Azevedo, Silvia Maria [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2020)
The letters published in the Portuguese-Brazilian press throughout the 19th and early 20th centuries were widely used by journalists-correspondents on both sides of the Atlantic. Jaime Vitor, one of the directors of Brazil-Portugal (1899-1914), used this discursive modality in the Letters from Rio de Janeiro, an open correspondence sent to the readers of the monarchist magazine, at a time when the Republic was established in Portugal. The purpose of the article is to offer a reflection on this textual genre focused on communication in a public space, considering the goals of Jaime Vitor's trip to the Federal Capital, in 1912, to strengthen the ties between Brazil and Portugal, exposed in the Letters from Rio de Janeiro.
Keywords: Open letter; Portuguese-Brazilian press; Jaime Vitor